Trueman's UGC CSIR-NET Life Sciences (Biology) - Pramod Singh (New Delhi Dhanika publishing, 2018)
Singh. P's Trueman's UGC CSIR-NET Life Sciences 1st Edition is a comprehensive book for CSIR - UGC NET/JRF aspirants. The book comprises of model question papers and exclusive questions for the students. In addition, there are multiple chapters that help in giving you a clear understanding of various concepts. This book is essential for candidates applying for CSIR - UGC NET/JRF and other competitive exams.
Syllabus Model Question Paper MCQs' on General Aptitude (Logical Reasoning, Graphical Analysis, Analytical and Numerical Ability, Quantitative Comparisons, Series Formation, Puzzles) Chapter 1 Molecules and their Interaction Relevant to Biology Chapter 2 Cellular Organisation Chapter 3 Fundamental Processes Chapter 4 Cell Communication and Cell Signaling Chapter 5 Developmental Biology Chapter 6 System Physiology - Plant Chapter 7 System Physiology - Animal Chapter 8 Inheritance Biology Chapter 9 Diversity of Life Forms Chapter 10 Ecological Principles Chapter 11 Evolution and Behaviour Chapter 12 Applied Biology Chapter 13 Methods in Biology Exclusive Questions for Part-C
Keywords: Life Science